School failure of disadvantaged students from a critical discourse analysis approach - Ignacio Calderón Almendros; Olga Cruz Moya; María Teresa Rascón Gómez (Arizona State University, 2019)
This article arises from a biographical qualitative approach with students in situation of socio-cultural disadvantage who suffer academic failure. Its aim is to explore the language used by these children from the perspective of critical discourse analysis, as well as to analyze the linguistic strategies chosen in representing social actors and actions, and linguistic-discursive features. In addition, speakers create a more strengthened discourse of their own group from a semiotic perspective, as opposed to the hierarchy and depersonalization in their relationships with the educational institutions. The distance between the language of school requests and the language they use within their primary groups favors failure and isolation.